Challenges and opportunities in graduate nursing education by distributed learning in Canada and Brazil - Molzahn, Anita; Macdonald, Marjorie; Banister, Elizabeth; Sheilds, Laurene; Starzomski, Rosalie; Brown, Marilyn; Gamroth, Lucia; Paskulin, Lisiane Girardi; Silveira, Denise Tolfo (Revista Gaúcha de Enfermagem, 2010)
In this paper, the authors share their experience related to graduate nursing programs offered by distributed learning (DL) in Canada and Brazil. Although degrees offered by DL are often the subject of criticism, the authors’ experience has been that learning outcomes have been very good. Nevertheless, a number of challenges and opportunities have been encountered including those associated with flexibility of the program, delivering practice courses at a distance, facilitating interaction, faculty workload and preparation and student support, Newer technologies that may assist in this effort are identified. Despite the challenges encountered, students rate the program highly and ongoing efforts are underway to ensure excellence of such flexible innovative graduate programs in nursing. The authors argue that despite the challenges, DL programs offer high quality graduate education that meets the needs of many nurses.